Utilizing the Kili-Kili Coastal Area as a Living Laboratory: Integrating Hydro-Climatological Stressors into the Geography Curriculum - Yesi Yuniar; Puspa Dewi Maharani; Sule Haruna Bibot; Agung Nugroho Biantoro (Future Space: Studies in Geo-Education, 2025)
Understanding the complex interaction between hydro-climatological stressors and agricultural productivity is crucial not only for environmental management but also for fostering geospatial literacy. This study aims to analyze the effects of seawater intrusion and Oldeman climate typology on agricultural productivity in Kili-Kili, Trenggalek, and evaluate these findings as a Contextual Teaching and Learning (CTL) resource. Using a descriptive-explorative design, water quality data (Salinity/TDS) and 10-year rainfall records (2015–2024) were analyzed and mapped against the Indonesian Kurikulum Merdeka learning outcomes. Scientifically, the region is classified as Oldeman Type D2 (3–4 wet months), creating a "double-stress" environment where salinity intrusion intensifies during the extended dry season. This condition correlated with a 27.2% decline in water-intensive rice yields, while resilient crops like cassava thrived. Pedagogically, these distinct spatial gradients and seasonal adaptations provide authentic empirical data for Geography Phase F curriculum, particularly for topics on Hydrosphere Dynamics and Food Security. We conclude that Kili-Kili serves as a vital "living laboratory." Transforming these local datasets into instructional materials bridges the gap between abstract theory and reality, effectively enhancing students' disaster resilience literacy.